Triglyceride to High-Density Lipoprotein Cholesterol (TG/HDL-C) Ratio, a Simple but Effective Indicator in Predicting Type 2 Diabetes Mellitus in Older Adults - Liu, Hongzhou; Liu, Jing; Liu, Jixiang; Xin, Shuanli; Lyu, Zhaohui; Fu, Xiaomin (Frontiers in Endocrinology, 2022)
Background: A simple and readily available biomarker can provide an effective approach for the surveillance of type 2 diabetes mellitus (T2DM) in the elderly. In this research we aim to evaluate the role of triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio as an indicator for new-onset T2DM. Methods: This secondary retrospective cohort study was conducted using a free database from a health check screening project in China. Participants with baseline TG and HDL measurements were enrolled, and the data of T2DM development were collected. The cumulative incident T2DM rates in different quintile groups of TG/HDL-C ratio (Q1 to Q5) were calculated and plotted. The independent effect of baseline TG/HDL-C ratio on T2DM risk during the follow up period was tested by the Cox proportional hazard model. Subgroup analysis was also conducted to clarify the role of TG/HDL-C ratio in specific populations. Results: A total of 231 individuals developed T2DM among 2,571 subjects aged over 75 years during follow up. Regardless of adjustment for potential confounding variables, elevated TG/HDL-C ratio independently indicated a higher risk of incident T2DM (hazard ratio (HR) = 1.29; 95% confidence interval (CI), 1.14 - 1.47; P < 0.01). As compared with the lowest quintile (Q1), elevated TG/HDL-C ratio quintiles (Q2 to Q5) were associated with a larger HR estimates of incident T2DM (HR (95% CI), 1.35 (0.85 - 2.17), 1.31 (0.83 - 2.06), 1.85 (1.20 - 2.85) and 2.10 (1.38 - 3.20) , respectively). In addition, a nonlinear correlation was found between TG/HDL-C ratio and the risk of T2DM and slope of the curve decreased after the cut-off point of 2.54. Subgroup analysis revealed a stronger positive correlation among male individuals and those with body mass index < 24 kg/m2. Conclusions: Increased TG/HDL-C ratio indicates a greater risk of new-onset T2DM regardless of confounding variables. TG/HDL-C ratio is a simple but effective indicator in predicting type 2 diabetes mellitus in older adults. More future investigations are warranted to further promote clinical application of TG/HDL-C ratio.